Flight of the puffin - Braden, Ann (Nancy Paulsen Books, 2021)
Told in multiple voices, seventh-grader Libby sets off a chain of events that brings hope and encouragement to four different individuals across the country who are dealing with bullies, acceptance, homelessness and grief.